Essays on innovation and business cycles - Gupta, Apoorva (2019)
This thesis contains three essays on the drivers of innovation and growth during business cycle downturns. It brings evidence from the Great Recession, the strongest downturn since the 1930s, and focuses on the case of Spain, a country that was seriously hit by the recession.